PENGGUNAAN MEDIA E–COMIC UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 4 MI AL-ADZIIM - Nurwaliyah, Wilan; Koswara Adiredja, Rajji; Widyaningsih, Yenni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading skills are part of a literacy culture that must be cultivated from an early age. However, the reality on the ground shows that many elementary school students still experience difficulties with reading comprehension. This study aims to improve the reading comprehension skills of fourth-grade elementary school students through the use of e-comics. This is motivated by the students' low ability to understand reading content in Indonesian language lessons. The method used was Classroom Action Research (CAR), implemented in two cycles, with stages of planning, implementation, observation, and reflection. The study subjects were 19 fourth-grade students. Data were collected through reading comprehension tests and student response questionnaires regarding learning using e-comics. The results showed that the use of the e-comic entitled "A Pair of Goodness Sandals" was effective in improving the reading comprehension skills of fourth-grade elementary school students. In the initial (pre-cycle) phase, students' reading comprehension skills were still relatively low, with an average score of 50.59 and a completion rate of 0%. After the interventions in Cycle I, the average score increased to 72.24 with a completion rate of 37%, although this increase was still in the moderate category. Then, in Cycle II, students' reading comprehension skills increased significantly, with an average score of 87.76, a completion rate of 100%, and an N-Gain of 0.75, which is considered high. These results indicate that the implementation of e-comics not only improves learning outcomes quantitatively but also helps students comprehend reading content at various levels.